2017
DOI: 10.1515/zpch-2017-1030
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Solid-State NMR, Dielectric Spectroscopy and Calorimetric Study of Water in Lowly Hydrated MCM-41 Samples

Abstract: The processes of drying mesoporous silica materials and their refilling with water have been examined by magic-angle spinning (MAS) solid-state NMR, broadband dielectric spectroscopy (BDS), and differential scanning calorimetry (DSC). It is shown that different drying protocols strongly influence the amount and types of hydroxy-species inside the pores. It is found that a very good vacuum (≈10−6 bar) is necessary to remove all H2O molecules from the silica matrices in order to accurately refill them with very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 33 publications
2
39
0
Order By: Relevance
“…MCM-41 compounds with various pore diameters d were synthesized and characterized by the Buntkowsky group (TU Darmstadt). Details can be found in another contribution to this issue [34]. Moreover, atomic layer deposition was employed by the Hess group (TU Darmstadt) to alter the chemical structure of the inner surfaces for some of the used MCM-41 materials, specifically, to deposit Al 2 O 3 layers, as again detailed in another contribution to this issue [35].…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…MCM-41 compounds with various pore diameters d were synthesized and characterized by the Buntkowsky group (TU Darmstadt). Details can be found in another contribution to this issue [34]. Moreover, atomic layer deposition was employed by the Hess group (TU Darmstadt) to alter the chemical structure of the inner surfaces for some of the used MCM-41 materials, specifically, to deposit Al 2 O 3 layers, as again detailed in another contribution to this issue [35].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Alternatively, it can be a consequence of distorted local structure and reduced density in solid confinement. Finally, for glycerol, it can result from water admixture during the filling process, although we exercised great care to start from dry mesoporous silica [34]. 2 H NMR was also employed to study glycerol dynamics in microemulsion droplets [38].…”
Section: Confined Glycerolmentioning
confidence: 99%
“…This suggests that not all NH 2 groups of the surface‐bound APTES linker reacted with glycine. This is consistent with our previous reports, in which we have found that not all linker groups are available for reaction, as well as with the work of Zagdoun et al., who have found an incomplete conversion of azide groups, which they have attributed to the inaccessibility of some of these surface groups. At this point it must be remarked that all 15 N chemical shifts, for the different reaction steps, can vary to a certain degree.…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H FLSG spectrum of the wet sample (Figure , wet) shows five diagonal peaks at around 0.8, 1.8, 3.4, 5.0, and 6.8 ppm. From our previous works, it is known that the peak at 0.8 ppm can be attributed to non‐hydrogen‐bound water and the peak at 1.75 ppm represents the silanol groups of the silica surface. Furthermore, the peak at around 3–3.5 ppm corresponds to water molecules in fast exchange between liquid and adsorbed state .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation